الخصائص الميكانيكية لمركبات( البولي استر غير المشبع/مادة مالئة) المسلحة بالألياف الزجاجية - علي, علي محمد; محمود, حبيب محمد; ابراهيم, نوار شوكت (Latakia University Journal -Engineering Sciences Series, 2016)
يـهدف هذا البحـث إلى دراسـة تأثير إضـافة المـواد المالئة (سـيليــكات الألمـــنيوم الصــوديوم والتـالك) على البولي استر غـــير الـمشـــبع (Unsaturated Polyester Resin)(UPR) أولاً، وعـلى البولي استر غير المشبع المقوى بالألـياف الزجـاجية بنـسبة20%) ) ثانياً، حـيث أجريت مجـموعة من الاختبارات الميكانيكية شملت (اختبار الشد والانحناء)، في المرحلة الأولى من البحث تمّ دراسة تأثير إضافة المواد المالئة، سيلــيكات الألمـنيوم الصـوديوم (SAS) والـتالك ومزيـج سيليـكات الألمـنيوم الصـوديوم والـتالك، على البولي استر غير المشبع الغير المقوى بالألياف الزجاجية، وقد أظهرت النتـائج أن أفضـل القيـم تمّ الـحصول عليها, عند إضافة مزيـج سيليكات الألمـنيوم الصـوديـوم والـتـالك وفق النسبة (5% Talc, 10% SAS)، حـيث ارتـفعت قيمـة مـتانة الـشد من(31.2 MPa) إلى ((33 MPa، وارتفعت قيمة معامـل المـرونة أيضاً من(330 MPa) إلى (2750.5 MPa) وكـذلك ارتـفعت قيمة متانة الانحناء من (0.057 GPa) إلى(0.0729 GPa). في المرحلة الثانية تمّ دراسة تأثير إضافة المواد المالئة )سيليكات الألمـنيوم الـصوديوم والتالك، ومزيـج سيلـيكات الألـمنيوم الصـوديوم والـتالك)، على البولي استر غير المشبع المقوى بالألياف الزجاجية بنسبة (20%)، وقد أظهرت النتـائج أن أفضـل القيـم تمّ الـحصول عليها عند إضافة مزيج سيلــيكات الألمـنيوم الصـوديوم والـتالك وفق النسبة (5% Talc, 5% SAS)، حيث ارتفعت قيـمة متـانة الـشد من 101.7 MPa)) إلى ((108.8 MPa، وارتفعت قيمة معامل الـمرونة أيضاً من (5616 MPa) إلى (6367.9 MPa) ، وكذلك ارتفعت قيـمة مـتانة الانحناء من (0.1203 GPa) إلى ((0.1597 GPa. This research aims to study the effect of addition the filling materials (sodium aluminosilicate, Talc) to the unsaturated polyester(unsaturated polyester resign)(UPR) first, and unsaturated polyester reinforced by fiberglass (20%) secondly, Number of mechanical tests were done, they included (Tensile, Flexural Strength). The effect of addition of filling materials sodium aluminosilicate (SAS), Talc, and a mixture of sodium aluminosilicate and Talc to the unreinforced polyester with fiberglass was studied in the first step of the research, and the results showed that the best values were gotten when adding a mixture of ((SAS) and Talc) at ratio (10% SAS,5% Talc), where the tensile strength value raised up from (31.2 MPa) to (33 MPa), and the elastic module value also raised up from (2330 MPa) to (2750.5 MPa) , and the flexural strength value also raised up from (0.057 GPa) to (0.0729 GPa). The effect of addition of filling materials (sodium aluminosilicate, Talc, and a mixture of sodium aluminosilicate and Talc ) to the reinforced polyester with fiberglass (20%) was studied in the second step of the research, and the results showed that the best values were gotten when adding a mixture of ((SAS) and Talc) at ratio (5% SAS,5% Talc), where the tensile strength value raised up from (101.7 MPa) to (108.8 MPa), and the elastic module value also raised up from (5616 MPa) to (6367.9 MPa), and the flexural strength value raised up from (0.1203 GPa) to (0.1597 GPa).